Japan’s policy towards North Korea under the Second Abe Administration - Żakowski, Karol (Asia in World Politics: Past, Present, and Future, 2021)
The aim of this chapter is to examine the efficiency of Prime Minister Abe’s hardline policy towards North Korea under his second administration. The analysis is conducted through the lenses of neoclassical realism. Apart from domestic factors (Abe’s “hawkish” convictions and anti-North Korean moods among the public in Japan), external stimuli will be examined, such as the US’s sudden shift towards soft-power policy vis-à-vis Pyongyang under the Trump administration and its impact on Tokyo’s foreign policy. It is argued that while ideological leanings of decision makers influenced the pace and intensity of diplomatic endeavors, it is the international determinants that delineated the general course of Japan’s foreign policy.